The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1590/s0100-204x2007000400017
|View full text |Cite
|
Sign up to set email alerts
|

Vitamina E no desempenho, características de carcaça e qualidade do presunto cozido de suínos

Abstract: Vitamin E on performance, carcass characteristics and quality of pig's cooked hamAbstract -The objective of this work was to evaluate the effect of vitamin E on performance, carcass characteristics and cooked ham quality. Ninety-six pigs were submitted to the following treatments: control; 100, 200 and 400 mg of vitamin E per kg of diet; during 116 days before slaughter. After slaughter, pig carcasses were measured, chilled, deboned and ham sections were removed to produce the cooked ham. Samples of frozen and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
0
2
0
3
Order By: Relevance
“…In a study of Souza et al (5), when evaluating different levels of vitamin E in the diet of pigs in the growing and termination phases, was found a linear increase in carcass yield with supplementation of up to 400 mg of vitamin E per kg of feed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study of Souza et al (5), when evaluating different levels of vitamin E in the diet of pigs in the growing and termination phases, was found a linear increase in carcass yield with supplementation of up to 400 mg of vitamin E per kg of feed.…”
Section: Discussionmentioning
confidence: 99%
“…En un estudio de Souza et al (5), al evaluar diferentes niveles de vitamina E en la dieta de los cerdos en etapas de crecimiento y finalización, se halló un incremento lineal en el rendimiento de las canales con suplementación de hasta 400 mg de vitamina E por kilogramo de alimento.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Recent studies suggested that dietary vitamin E may be a promising alternative to improve such parameters. Vitamin E is a powerful antioxidant and its supply in diets has resulted in lower meat lipid oxidation and drip loss and better meat color (Souza et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…O uso de antioxidantes como vitamina E, selênio e ácido ascórbico, fornecidos via dieta para os animais (Souza et al, 2007;Silva et al, 2013;Silva et al, 2015), e ácido fítico, presente nos próprios cereais que compõem a ração, têm comprovada capacidade de diminuir a oxidação da carne, melhorando sua qualidade (haRbaCh et al, 2007;PaCheCo et al, 2012).…”
Section: Introductionunclassified